Measuring the State Losses in Corruption Cases at the Village Credit Institutions in Bali - Widia, I Ketut (SASI, 2022)
Introduction: Until the end of 2021, the legal issue having been an actual trending topic and hot issue which attracts the attention of scholars and researchers, is the phenomenon of the emergence of criminal acts of corruption committed in congregation by the management of the Village Credit Institution in Bali. Generally, the resolution of these cases is carried out in a traditional manner with the spirit of local wisdom and kinship through the Paruman Krama of Traditional Villages to attain an agreement or consensus. The prosecutor’s office, however, enters into this customary realm, then participates in conducting preliminary investigations and investigations. The involvement of prosecutor is only on the basis of a document issued in 1988 regarding the Bali Governor’s Assistance amounting to two million rupiah as the initial capital for the establishment of the Village Credit Institution. Purposes of the Research: The present study aims at identifying whether or not the results of the regency inspectorate’s audit can be used as a basis for prosecuting suspects in the cases of abuse of Village Credit Institution finance as well as alternative solutions that necessarily need to be taken to resolve the cases. Methods of the Research: The first problem is examined using the Theory of Penalty and the second one is examined using the Theory of the Welfare State Law. The research method used is a mixed legal research method. Data are presented using a systematic description technique. Results of the Research: The solution that is expected is this study sheds light on whether or not the results of the regency inspectorate’s audit can be used as a basis for prosecuting suspects in cases of abuse of the Village Credit Institution finance, what factors are the causes of the liquidity crisis and wether the present study results can be applied as an alternative solution that should be taken in resolving cases at the regency level. The target to be achieved in the research is publication on the electronic media Bali TV in the regional seminar on “Menghitung Kerugian Negara dalam Kasus Korupsi Pada Lembaga Perkreditan Desa di Bali”. The expected output from the study is the results will be published in the Sinta I indexed journal.